This time is different chartbook: country histories on debt, default, and financial crises - National Bureau of Economic Research, Cambridge; Reinhart, Carmen M. (Cambridge, MA, 2010)
"This Chartbook provides a pictorial history, on a country-by-country basis, of public debt and economic crises of various forms. It is a timeline of a countrys creditworthiness and financial turmoil.The analysis, narrative, and illustrations in Reinhart and Rogoff (2009), This Time is Different: Eight Centuries of Financial Folly, were primarily organized around themes (serial default, inflation, etc.), although detailed tables in the book chronicled country-specific information on the dating, frequency, incidence, etc. of specific crises episodes by country. The Chartbook compliments the thematic analysis with individual country histories, and provides the grounds for a systematic analysis of the temporal patterns of debt cycles, banking and sovereign debt crises, hyperinflation, and, for the post World War II period, the reliance on IMF programs."